Interaction of Coastal Ethnoscience Learning and Ecological Attitudes in Elementary Science - Jumrah Jumrah; Imas Srinana Wardani; Prayogo Prayogo (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Science learning in elementary school should foster students’ conceptual understanding and critical thinking skills through contextual learning experiences. This study aimed to analyze the effect of coastal ethnoscience learning on elementary school students’ conceptual understanding and critical thinking skills in science, as well as to examine the interaction between coastal ethnoscience learning and ecological attitudes in influencing both outcomes from a school management perspective. This study employed a quantitative approach with a 2×2 factorial quasi-experimental design (pretest-posttest non-equivalent control group) involving 34 fourth-grade students at SDN 25 Moko, Raja Ampat. Data were collected through a conceptual understanding test, a critical thinking skills test, an ecological attitudes questionnaire, and were supported by observations of learning implementation. The data were analyzed using ANOVA and MANOVA after the prerequisite tests had been satisfied. The results showed that coastal ethnoscience learning had a significant effect on conceptual understanding (p = 0.006) and critical thinking skills (p < 0.001). In addition, there was a significant interaction between coastal ethnoscience learning and ecological attitudes on conceptual understanding (p = 0.017; η² = 0.010) and critical thinking skills (p = 0.045; η² = 0.071). These findings indicate that the effectiveness of coastal ethnoscience learning is influenced by students’ ecological attitudes. From a school management perspective, these results underscore the importance of school support in managing the potential of the coastal environment as a learning resource, strengthening ecological culture, and facilitating well-planned contextual learning to improve the quality of science learning in elementary schools.